The architecture of the church of St. Demetrius in New Belgrade (1998-2001): A new element of the city's identity - Aćimović Emilija (Nasleđe)
The Church of Saint Demetrius of Thessaloniki (1998-2001) was the first religious building to be constructed within the modern urban landscape of New Belgrade. The time of its creation was marked by a renewal of Orthodox Christian identity and the need for a greater number of new parish churches, especially within settlements built devoid of them during Socialist Yugoslavia. As the first such edifice in New Belgrade, the Church of St. Demetrius stood out not only for its artistic qualities, but also for changing the identity of the area. Communicating with the environment and the zeitgeist, as well as the rich Serbian sacral tradition, the project of architect Nebojša Popović (1950-1998) has been interpreted as a major threshold of contemporary church architecture in Serbia. Largely due to its visual, conceptual and symbolic impact, the church is undeniably deserving of historiographical attention.